THE IMPORTANCE OF THEATERING IN TEACHING A FOREIGN LANGUAGE TO STUDENTS - Ibragimova Dilafruz; Kurbonov Nasibullo (Galaxy International Interdisciplinary Research Journal, 2021)
The role of innovative technologies in terms of the students’ intercultural competence in the process of teaching foreign languages is studied. The peculiarities of the usage of drama as art-technology and its role for developing communication skills are analyzed. The informal and formal theatre, mime, improvisation and performance elements are described.